Gli edifici di culto tra salvaguardia delle garanzie e tutela del pluralismo. Un percorso di ricerca - Fabbri, Alberto (Cultura giuridica e diritto vivente, 2015)
[The places of worship between safeguarding the guarantees and protection of pluralism. A path of Research] The constitutional recognition of the right to religious freedom, that finds expression in the performance of acts of worship, relates the need expressed by an individual or a community to the national and regional legislation concerning the construction of places of worship. The great number of requests and a concept of ritual that, as it seems, tends to a wide-spectrum religious service, require that local authorities constantly change legislation so as to meet the demands, while fully respecting the urban regulations in force. As the balance between the different forces involved must be ensured, pending a law on religious freedom, the place of worship is, as a result, slowly undergoing a redefinition meeting the new religious needs to greater extent.